'Black sheep in the herd'? The role, status and identity of generalist doctors in secondary care. (November 2016) - Muddiman, Esther; Bullock, Alison; Allery, Lynne; MacDonald, Janet; Webb, Katie Louise; Pugsley, Lesley
Changing patient demographics raise important challenges for healthcare providers around the world. Medical generalists can help to bridge gaps in existing healthcare provision. Various approaches to medical generalism can be identified, for example, hospitalists in the US and the restructuring of care away from medical disciplines in the Netherlands, which have different implications for training and service provision. Drawing on international debates around the definition and role of generalism, this article explores one manifestation of generalism in the UK to understand how abstract ideas work in practice and some of the benefits and challenges. Broad-based training is a two-year postgraduate training programme for doctors recently piloted in England. The programme provided 6-month placements in four specialties (general practice, core medicine, psychiatry and paediatrics) and aimed to develop broad-based practitioners adept at managing complex and specialty integration. Our longitudinal, mixed methods evaluation of the programme demonstrates that although trainees value becoming more holistic in their medical practice, they also raise concerns about being perceived differently by co-workers, and report feeling isolated. Using identity theory to explore the interplay between generalism and existing boundaries of professionalism in healthcare provision, we argue that professional identity, based on disciplinary structure and maintained by boundary work, troubles identity formation for generalist trainees who transcend normative disciplinary boundaries. We conclude that it is important to address these challenges if generalism in secondary care settings is to realise its potential contribution to meeting increasing health service demands.